Feasibility study on intracranial pressure and prognosis of patients with moderate and severe craniocerebral injury using the Rotterdam computed tomography score: an observational study - Ni, Juan; Zhao, Wei; Wang, Zhifeng; Wang, Xuejian (Frontiers in Neurology, 2025)
ObjectiveThe Rotterdam computed tomography (CT) score was used to evaluate the degree of coma and the prognosis of patients with moderate and severe craniocerebral injury, to analyze its feasibility, and to assess its value in guiding further clinical applications.MethodsA total of 120 patients with moderate-to-severe craniocerebral injuries were selected as study participants, all of whom were treated at the Department of Neurosurgery of the Second Affiliated Hospital of Nantong University. All 120 patients underwent craniocerebral CT scans. The Glasgow Coma Scale was used to evaluate the degree of coma, and the Glasgow Outcome Scale was used to evaluate prognosis. The Rotterdam CT scores of patients with different degrees of coma and prognoses were compared.ResultsThe Rotterdam CT score was significantly lower in patients with moderate coma than in those with severe coma (p < 0.05). The Rotterdam CT score of patients with a good prognosis was significantly lower than that of patients with a poor prognosis (p < 0.05).ConclusionThe Rotterdam CT score is indicative of the degree of coma in patients with moderate and severe craniocerebral injuries and has prognostic value. The Rotterdam CT score also shows potential for broader clinical application.